PENDIDIKAN TANPA IDENTITAS DAN MEMBEBASKAN RETHINKING PENDIDIKAN MANUSIA SEUTUHNYA - Hasanah (Al'Adalah, 2014)
Education in terms of its goal never loose from the community who around it. The purpose of convention of education should always be used as reference education policy. When looking at the phenomena of education in indonesia apparently there is a tendency away from its main purpose the potential to grow the protege in order can face his future with brilliant. Macro policy education for instance the goal is still the subordination of the policies political and economic. As a result the pattern of the implementation of education national prevailing often the entry of imposing substance less educate. On the other side are still not precisely an understanding of religious education result in the occurrence of overlap between public education and religious education. This writing aims to encourage to think back a humanizing education. Education supposed to be the instrument of social and spiritual that serves give assurance maintenance man who has faith and knowledge. Ideally education in indonesia able to give insight to humanize man in accordance with his creation tendency as creatures free and cultured.